The genus Anathallis (Orchidaceae: Pleurothallidinae) in Mexico - Solano Gómez, Rodolfo; Licona, Ethian (2023)
Anathallis encompasses nearly 120 neotropical orchid species, with Mexico representing the northernmost limit of its distribution. Around fifteen Mexican species were initially classified in Anathallis during the current century. However, several of them have been reclassified in recent years into Lankesteriana, Specklinia, and Stelis. Currently, Anathallis in Mexico includes A. greenwoodii, A. lewisiae, A. minutalis, A. oblanceolata, A. sertularioides, and A. yucatanensis. This work presents the taxonomic treatment for these species, models of their potential distribution, and the assesses of their conservation status in Mexico. For this, specialized literature, living and herbarium specimens, and online databases were examined. For each species, a description, drawing, photograph, and distribution map were prepared, along with information on nomen-clature, habitat, phenology, comparison with similar species, and an assessment of their risk status is provided. Mexican Anathallis plants are characterized by their diminutive habit, rhizomatous growth, semi-open flow-ers with acute sepals and petals, free lateral sepals, mobile lip, and winged column. Five species are recognized among them: A. lewisiae, A. minutalis, A. oblanceolata, A. sertularioides, and A. yucatanensis. Anathallis greenwoodii exhibits a morphology more similar to Lankesteriana and it was transferred accordingly. Anathallis oblanceolata was previously known only from the type locality and is redescribed based on specimens previously confused with A. minutalis. Both species are endemic to the mountainous regions of Mexico. Anathallis lewisiae,A. sertularioides, and A. yucatanensis grow in warm, lowland areas along the Gulf of Mexico coast and Yucatan Peninsula. The extinction risk assessment assigned the category of species subject to special protection to the five Mexican taxa. For each taxon the extent of its distribution in Mexico and the environmental variables determining...
Anathallis incluye casi 120 especies de orquídeas neotropicales y México representa el límite norte de su distribución. Durante el presente siglo, hasta quince especies mexicanas han sido clasificadas en Anathallis. Pero en los último años varias de ellas han sido reclasificadas a géneros como Lankesteriana, Specklinia y Stelis. Actualmente Anathallis de México incluye A. greenwoodii, A. lewisiae, A. minutalis, A. oblanceolata, A. sertularioides y A. yucatanensis. Este trabajo presenta el tratamiento taxonómico para dichas especies, el modelado de su distribución potencial y la evaluación de su estatus de conservación en México. Para ello se revisó literatura especializada, especímenes vivos y registros en colecciones científicas y bases disponibles en línea. Para cada especie se presenta una descripción, dibujo, fotografía, mapa de distribución; además, se proporciona información sobre su nomenclatura, hábitat, fenología, comparación con especies similares y una evaluación de su estatus de riesgo. En México las plantas de Anathallis se caracterizan por su hábito diminuto, crecimiento rizomatoso, flores semiabiertas con sépalos y pétalos agudos, sépalos laterales libres entre sí, labelo móvil y columna alada. El género incluye cinco especies mexicanas: A. lewisiae, A. minutalis, A. oblanceolata, A. sertularioides y A. yucatanensis. Anathallis greenwoodii exhibe una morfología más similar con Lankesteriana y por ello se transfiere a este género. Anathallis oblanceolata solo era conocida de la localidad tipo, aquí se redescribe a partir de especímenes previamente confundidos con A. minutalis. Ambas especies son endémicas en las zonas montañosas de México. Anathallis lewisiae, A. sertularioides y A. yucatanensis crecen en zonas cálidas y bajas de la costa del Golfo de México y Península de Yucatán. La evaluación del riesgo de extinción asignó la categoría de especie sujeta a protección especial a los cinco...
Keywords: ORQUIDEAS -- MEXICO; ORQUIDEAS -- CLASIFICACION -- MEXICO; ORQUIDEAS -- CONSERVACION -- MEXICO; PLANTAS ENDÉMICAS -- MÉXICO